How to cope with mobility expectations in academia: individual travel strategies of tenured academics at Ghent University, Flanders - Storme, T.; Beaverstock, J.V.; Derudder, B.; Faulconbridge, James R.; Witlox, F.
The production and exchange of knowledge are inextricably linked to different compulsions to corporeal proximity and therefore travel. As primary producers and transferors of knowledge, academics are no exception to this rule, and their compulsions seem to be further propelled by institutional discourses regarding the alleged virtues of “internationalization.” Tenured academics, moreover, have a high degree of independence and can therefore easily choose how to cope with compulsions and constraints to internationalize. However, the business-travel literature has paid scant attention to academics and their individual contexts. In an effort to rectify this situation, this paper explores a travel dataset of tenure-track academics (N=870) working at Ghent University. The insights emerging from this analysis are then contextualized by complementing them with in-depth interviews of tenured academics (N=23) at the same institution. This paper argues, first, that varying compulsions and constraints at home and abroad lead to distinct non-travel and travel-intensive academic roles. And second, that academics who have difficulties coping, try to rationalize their corporeal travel behaviour and their mobility behaviour to meet the needs and expectations to internationalize. These strategies give an indication of how travel-related working practices can become more efficient and sustainable in the future.